1082 Are Trauma and Orthopaedics Consultant Posts Decreasing in Frequency and Increasing in Subspecialisation?. (12th October 2021) - Ansari, S A; Kennedy, J; Irwin, B; Rogers, S
Abstract: Aim: Changes to the configuration of the NHS Trauma Services in T&O and the level of subspecialisation are changing and could impact training and the number of consultant posts available at CCT. The aim of this study was to review the number of T&O Consultant posts and determine the frequency of the subspecialist requirements of these posts from 2011 to 2020, to assess the perceived reduction in advertised numbers and the increasing sub specialisation as a whole. Method: 451 volumes of the BMJ were reviewed over Jan 2011 - April 2020. The total number of jobs advertised were recorded. Additionally, for each post, sub-specialism, regional analysis and substansive or locum tenure were recorded. Results: 1141 jobs were advertised during this period. There has been a decreasing trend in the total number of advertised posts of 13% per annum. Proportion of specialty jobs remain constant yearly. However, jobs listing Trauma clearly decreased after 2012, when trauma centres were initiated. Clear decreases were present in North-west and Scotland in number of jobs. There has also been an increasing trend of advertisement of substantive posts, with locum posts forming less than 13% of total advertisements. Conclusions: We found no significant increase in job specialism contradicting previous research. Overall, the total number of Consultant jobs in Trauma and Orthopaedics is decreasing, especially in the north-west and Scotland, two of the biggest employers. Questions must be asked for the future of training in T&O to meet service needs.